Imaging features of superior mesenteric artery syndrome: a rare vascular compression disorder - Suresh, Naina; Nanjundan, Murali; Natarajan, Sundari; Chandrasekaran, Subhashree (International Surgery Journal, 2016)
Superior mesentric artery (SMA) syndrome is an extremely rare acquired vascular compression disorder with a prevalence of around 0.1-0.3%. The transverse or D3 segment of the duodenum crosses between the aorta and SMA between the Aortomesentric angle (AMA) maintained by the retroperitoneal fat. Various clinical scenarios causing reduction in the AMA make the patient vulnerable to the syndrome. Two young female patients referred to the emergency department with history of abdominal pain and vomiting were imaged with with ultrasonography and Contrast enhanced Computed Tomogram (CT) of the abdomen and pelvis with CT abdominal angiography. The Aortomesentric angle (AMA) on sagittal MPR MIP images and the Aortomesentric distance (AMD) on axial images was calculated.Both the patients had similar imaging findings which included gross dilatation of the stomach with circumferential gastric wall thinning and gastric rugal flattening, dilated duodenum upto the transverse or D3 segment with abrupt narrowing of the third part of duodenum at the level of SMA crossing. The AMD calculated on axial images between the SMA anteriorly and the aorta posteriorly at the point where the duodenum crosses the aorta and the AMA calculated on sagittal MPR MIP images were reduced. SMA syndrome is a rare acquired vascular compression disorder due to decreased AMA due a myriad of clinical scenarios. Multidetector CT with angiography is the imaging modality of choice. Ultrasonography and upper gastrointestinal barium studies serve as additional diagnostic tools. Initial treatment is conservative with fluid and electrolyte resuscitation. The surgical option of choice is laparoscopic Duodenojejunostomy.